2002
DOI: 10.1046/j.1471-6712.2002.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma nurse practice improves outcomes and reduces costs in primary health care

Abstract: This alternative asthma strategy, ANP, improved asthma care in primary health care and resulted in economic advantages in the health care sector. However the result may only be generalized to other practices working with asthma nurses in the same way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 18 publications
1
60
0
3
Order By: Relevance
“…To the best of the authors9 knowledge this is the first study on childhood asthma in which traditional physician care was substituted by nurse-led care, resulting in a reduction of healthcare costs. This confirms previous studies in which nurse-led care in adults with selected chronic disorders in primary care was more cost-effective than traditional physician-led care [34][35][36]. In secondary care results in adults have been conflicting.…”
Section: Discussionsupporting
confidence: 85%
“…To the best of the authors9 knowledge this is the first study on childhood asthma in which traditional physician care was substituted by nurse-led care, resulting in a reduction of healthcare costs. This confirms previous studies in which nurse-led care in adults with selected chronic disorders in primary care was more cost-effective than traditional physician-led care [34][35][36]. In secondary care results in adults have been conflicting.…”
Section: Discussionsupporting
confidence: 85%
“…221,227 The majority (n = 9) were conducted in primary care or community settings, 218,219,226,228,229,[234][235][236] four in managed care organisations (MCOs), 220,222,223,225 one in secondary care, 230 three in schools 221,224,231 and one (two reports) was a national multisetting initiative.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…228 Seven were based on longitudinal data, 220,223,[230][231][232][233][234][235] one with a control cohort, 229 and two uncontrolled before-and-after 221,236 or cross-sectional studies. 227 This resulted in substantial variation in quality assessment, ranging from 10 to 24 out of a possible score of 28. 48 Common reasons for low quality included lack of information on participants lost to follow-up (n = 15) and/or whether participants were representative of the whole eligible population (n = 11).…”
Section: 233mentioning
confidence: 99%
See 1 more Smart Citation
“…10 The Swedish Respiratory Group in Primary Care established criteria for asthma clinics in 1998, 10,11 and these criteria have been used to define asthma clinics in this study. Studies evaluating asthma clinics have demonstrated improvements in some aspects of asthma control, [12][13][14] and the need for more good quality trials has been highlighted. 15 Previous studies on changes in quality of life have not been able to show improvements in patients attending asthma clinics.…”
Section: Introductionmentioning
confidence: 99%